Community livelihood recovery experiences from 2006 Guimaras oil spill in the Philippines - Sacramento, Noe John Joseph (Journal of Human Ecology, 2019)
The 2006 oil spill in Guimaras, Philippines, ravaged coastal communities, causing loss of fishing resources, and pollution of the coastal environment. This case study examines the community’s live- lihood recovery efforts after the disaster. The “Build, Back, Better” approach (Clinton, 2006) provided the lens to describe the stakeholder’s participation and empowerment for inclusive and planned community livelihood recovery. The study focuses on Barangay La Paz, Nueva Valencia, Guimaras, a profoundly affected coastal settlement during the oil spill in 2006. Key Informant Interviews (KII), Focus Group Discussions (FGD), and secondary data collected from published research reports and government documents are the major data sources. The study employs thematic analysis. The find- ings reveal that various actors involved in community livelihood recovery provide alternative sources of income and help restore the livelihood sector. Building the community’s sense of ownership in the recovery process is shaped by several push and pull factors and thus also affects the sustainability objectives of the livelihood. Conditions for the release of financial assistance and claims are crucial to alternative and sustainable community livelihood recovery. Participatory planning involving the fishers themselves in deciding the terms and directions of the initiatives is strategic and important for sustainability. In gist, community livelihood recovery effort entails a chain of responsibilities among actors in the process. Recommendations for sustained community livelihood recovery based on the lessons from this case are provided for humanitarian organizations.